Designing feedback : performance measures for continuous improvement - Thor, Carl G. (Crisp Pub. Menlo ParkUS, 1998)
Addresses issues of feedback such as flow and frequency, accuracy and gathering effort, individual and group measures, and style and format. Describes types of performance measures including: profitability measures, measures of process quality, and workforce measures. Explains how measures are used and emphasises the need for vertical communication of measured results.